A modified SDS-based DNA extraction method from raw soybean. Issue 2 (5th February 2019) - Xia, Yimiao; Chen, Fusheng; Du, Yan; Liu, Chen; Bu, Guanhao; Xin, Ying; Liu, Boye
Abstract : Soybean is the most important genetically modified (GM) oilseed worldwide. Regulations relating to the approval of biotech soybean varieties and product labeling demand accurate and reliable detection techniques to screen for GM soya. High-quality extracted DNA is essential for DNA-based monitoring methods. Thus, four widely used protocols (SDS, CTAB, DP305, and DNeasy Plant Mini Kit) were compared in the present study to explore the most efficient DNA extraction method for raw soya matrix. The SDS-based method showed the highest applicability. Then crucial factors influencing DNA yield and purity, such as SDS lysis buffer component concentrations and organic compounds used to isolate DNA, were further investigated to improve the DNA obtained from raw soybean seeds, which accounts for the innovation of this work. As a result, lysis buffer (2% SDS (w/v), 150 mM NaCl, 50 mM Tris/HCl, 50 mM EDTA, pH 8.0) and organic reagents including chloroform/isoamyl alcohol (24:1, v/v) (C: I), isopropanol, and ethanol corresponding to the extraction and first and second precipitation procedures, respectively, were used in the optimized SDS method. The optimized method was verified by extracting approximately 2020–2444 ng DNA/mg soybean with A260/280 ratios of 1.862–1.954 from five biotech and non-biotech soybean varieties. Only 0.5 mg of soya was required to obtain enough DNA for PCR amplification using the optimized SDS-based method. These results indicate that the screening protocol in the present study achieves the highest suitability and efficiency for DNA isolation from raw soya seed flour.